2006
DOI: 10.1115/1.2346691
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Nonlinear Oscillations for Viscoelastic Moving Belt Using Generalized Hamilton’s Principle

Abstract: In this paper, the nonlinear governing equations of motion for viscoelastic moving belt are established by using the generalized Hamilton’s principle for the first time. Two kinds of viscoelastic constitutive laws are adopted to describe the relation between the stress and strain for viscoelastic materials. Moreover, the correct forms of elastic strain energy, kinetic energy, and the virtual work performed by both external and viscous dissipative forces are given for the viscoelastic moving belt. Using the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Actually, the standard linear solid model, which can describe the behavior of linear viscoelastic materials of solid type with limited creep deformation, covers the Kelvin model and the integral-type constitution relation with an exponential relaxation function as special cases. When differential-type constitutive laws are incorporated, some investigators used the partial time derivative in the viscoelastic constitutive relations [2][3][4][6][7][8]11,12,14,15,20,21,23,24]. However, Mochensturm and Guo [18] demonstrated that the material time derivative should be used to account for the additional "steady state" dissipation of an axially moving viscoelastic string.…”
Section: Introductionmentioning
confidence: 97%
“…Actually, the standard linear solid model, which can describe the behavior of linear viscoelastic materials of solid type with limited creep deformation, covers the Kelvin model and the integral-type constitution relation with an exponential relaxation function as special cases. When differential-type constitutive laws are incorporated, some investigators used the partial time derivative in the viscoelastic constitutive relations [2][3][4][6][7][8]11,12,14,15,20,21,23,24]. However, Mochensturm and Guo [18] demonstrated that the material time derivative should be used to account for the additional "steady state" dissipation of an axially moving viscoelastic string.…”
Section: Introductionmentioning
confidence: 97%
“…Different models have been exploited to express the constitutive relations of the homogeneous viscoelastic materials such as the differential models, Chen et al (2007), Boltzmann superposition integral model, Hamed (2012) and Lei et al (2013a, b) or fractional viscoelasticity models, Ezzat et al (2013) and Ansari et al (2015Ansari et al ( , 2016. On the other side, many papers adopted the correspondence principle and Laplace transformation methods such as Kiasat et al (2014) and Khazanovich (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different nonlinear models of transverse vibration of axially moving strings were adopted to investigate energetics and conserved quantities [10,11]. Besides, governing equations can be derived from the energy principle [12]. The conserved quantities were applied to check numerical schemes [13][14][15] and to analyze the stability [11].…”
Section: Introductionmentioning
confidence: 99%